Cardiovascular magnetic resonance for the assessment of coronary artery disease. (15th August 2015) - Gotschy, Alexander; Niemann, Markus; Kozerke, Sebastian; Lüscher, Thomas F.; Manka, Robert
Abstract: Over the past decade, cardiovascular magnetic resonance (CMR) has become an established non-invasive imaging modality in cardiology. It provides clinicians and researchers with an unparalleled versatility of diagnostic parameters such as cardiac morphology, function, myocardial texture and vascular flow. One of the most relevant applications of CMR is the assessment of patients with suspected or known coronary artery disease (CAD). In large clinical trials, CMR has proven its robustness, diagnostic performance and prognostic value in CAD. In patients with known or suspected chronic CAD, detection of ischaemia and myocardial viability for guiding therapeutic decisions is a major strength of CMR. Patients with ischaemic congestive heart failure (CHF) may benefit from CMR for planning of device implantation or monitoring intracavital thrombi. Finally, the use of CMR in the emergency department for the assessment of patients with acute chest pain is an emerging field, in which CMR's capability to characterize myocardial tissue regarding e.g. necrosis, edema or microvascular obstruction (MVO) may prove clinically useful. The CMR technology is safe, free of ionizing radiation and proved higher diagnostic accuracy and superior cost efficiency compared with other standard diagnostic modalities. Highlights: CMR has made tremendous technical advances over the past decade. Myocardial ischaemia and viability can be assessed with a single CMR examination. Large trials proved excellent diagnostic accuracy of CMR in the evaluation of CAD. CMR has superior cost efficiency compared with other diagnostic modalities.